PEMBINAAN DAN PENGAWASAN PEMERINTAHAN KOTA PEKANBARU TERHADAP PERUSAHAAN DAERAH AIR MINUM TIRTA SIAK PEKANBARU TAHUN 2015 - Muhammad Arofah; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is based on the poor performance of PDAM Tirta Siak Pekanbaru from year to year. There are two main issues. Firts, the problem of inefficiency. That is the low water production amount, the disturbed water distribution due to the old pipe, then the occurence of corruption, etc. Second, the problem of guidance and supervision, namely the lack of assistance form the city government to PDAM Tirta Siak apart from the budget. With a budget that is not enough, making PDAM Tirta Siak Pekanbaru difficult to carry out coaching on employees. This study aims to determine the guidance and supervision of the city government of pekanbaru againts PDAM Tirta Siak Pekanbaru and the factors that influence the guidance and supervision. This research uses descriptive research type with qualitative research approach. The type of research data is primary data and secondary data. Data collection techniques in this study are documentation and interviews. Data analysis technique used is descriptive qualitative data analysis.The result showed that coaching from the city government pekanbaru has not run optimally. The PDAM own never get coaching from the goverment. Another case from the government where the provision of budget againts PDAM Tirta Siak Pekanbaru already include in the form of coaching. For self-monitoring has been going pretty well. There are inhibiting factors which are greater for low budget and human resources. The solution to solve the problem of guidance and supervision of the city government should be more optimal in coaching by coordinating with all relevant parties in progress. And supported by the budget of the government and quality human resources from both sides.Key Words: Government Coaching, Supervision, and PDAM